P-125 YI Dysregulated Estrogen Receptor Expression in Mucosal T Cells Leads to Female Sex Bias in an Experimental Model of Chronic Ileitis. (March 2016) - Goodman, Wendy; Kuang, Steven; Holmstrom, Jessica; Cominelli, Fabio; Pizarro, Theresa T.
Abstract : Background: Crohn's disease (CD) patients exhibit an increased frequency of Foxp3-expressing regulatory T cells (CD4 + CD25 + Foxp3 +, Tregs) in the intestinal mucosa, which show suppressive function ex vivo despite their failure to regulate chronic activation of effector T cells in situ. This suggests that factors present in the inflamed intestinal mucosa can disrupt normal Treg function in vivo. CD is disproportionate in female patients, suggesting that estrogen (E2) may contribute to worsened clinical disease. Despite this linkage, E2 has paradoxically been shown to be immunoprotective via induction of Foxp3 expression in conventional T cells (CD4 + CD25 −, Tconv). The goal of this study was to determine the mechanistic contribution of E2 signaling to T cells in female ileitis subjects and to test the hypothesis that enhanced E2 signaling to estrogen receptor beta (ERb) subverts normally immunoprotective functions of E2. Methods: We utilized the SAMP1/YitFc (SAMP) mouse model, a spontaneous model of ileitis that recapitulates many features of human CD including female sex bias. ERb-knockout mice were fully back-crossed to SAMP to generate congenic SAMP-ERb-KO mice. Tconv and Treg were isolated from the mesenteric lymph node (MLN) by flow cytometric sorting and used for downstream applications including real-time quantitative PCR (qPCR); chromatin immunoprecipitation (ChIP); and Next-Generation RNA Sequencing (RNA-Seq). Results: SAMP-ERβ-KO mice respond to E2 solely through the estrogen receptor alpha (ERα) isoform and not through ERb, making them a convenient tool to study the contribution of ERa/ERb signaling to ileitis. We observed significantly decreased ileal inflammation in 10-week-old SAMP-ERb-KO-F mice compared to native SAMP-F, resulting in a loss of female sex bias and a restoration of MLN Tregs in SAMP-ERb-KO mice. qPCR analysis revealed that Tconv from native SAMP-F express significantly lower ERα and higher ERβ mRNA levels compared to SAMP-M, leading to an overall increase in ERβ/ERα ratios in native female SAMP. Interestingly, SAMP-ERβ-KO mice displayed equivalent ERa gene expression among male and female Tconv, further implicating elevated expression of ERβ as a potential contributor to the female sex bias in SAMP. Additionally, ChIP assays revealed faulty transcription-factor binding of E2 to target gene promoters in Tconv from native SAMP-F, suggesting that nuclear factor activity of ER is compromised in SAMP-F. RNA-Seq experiments using MLN Tregs revealed distinct patterns of gene expression among native male and female SAMP, as well as among SAMP-ERb-KO mice compared to native SAMP, suggesting that perhaps as a consequence of altered ERa/ERb expression, native SAMP-F Tregs display an aberrant genetic signature. Conclusions: The interplay between E2 and lymphocyte function is a relatively understudied area with the potential to uncover novel gene-regulatory mechanisms operating downstream of nuclear hormone receptors that may influence development of IBD and other autoinflammatory diseases. Collectively, our data suggest that E2-ERa signaling is immunoprotective in the setting of intestinal inflammation and that female sex bias persists due to elevated ratios of ERb/ERa expression in conventional T cells. Differential gene expression in male and female SAMP Tregs suggests that faulty E2 signaling in females results in aberrant Treg differentiation and/or function, contributing to worsened clinical disease.